Q. 114.5( 6 Votes )

Differentiate each of the following w.r.t. x:

(2x2 – 3x +4)5

Answer :

Formulae :






Let,


y = (2x2 – 3x + 4)5


and u = (2x2 – 3x + 4)


therefore, y = u5


Differentiating above equation w.r.t. x,


………… By chain rule



………….


= 5. (2x2 – 3x + 4)4. (4x-3+0) ………….


= 5. (2x2 – 3x + 4)4 (4x-3)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses